Enhancing student’s competence in writing autobiographies through interactive storytelling - Sutikno, Sutikno; Kartolo, Rahmat; Marpaung, Prama Nita; Harianto II (Jurnal Konseling dan Pendidikan, 2025)
The teaching of biographical recount texts in tenth grade often encounters obstacles such as low student comprehension, a lack of engagement in the learning process, and the use of conventional teaching methods that are less effective. This indicates a need for interactive learning media capable of enhancing student understanding and motivation. This research aims to develop interactive multimedia-based learning media for biographical recount text materials, which not only presents the material but also incorporates visual, audio, and video elements to increase student engagement. The focus of this study is to measure the effectiveness of the media in improving students' comprehension of biographical texts. This research employs the Research and Development (R&D) method, utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of the research were tenth-grade students at SMA Negeri 1 Tanjung Balai in the 2024-2025 academic year. Data were collected through questionnaires, learning achievement tests, and interviews. Effectiveness testing was conducted by comparing the learning outcomes of students who used interactive media with those who used conventional teaching methods. The results showed that interactive multimedia-based learning media had an effectiveness rate of 84.28%, which is categorized as very good. The average score of students who used the interactive media was 84.3, which is higher than the average score of students who used conventional methods, which was 65.1.